TRANSFORMATIVE TEACHERS AND DIFFERENTIATED ENGLISH INSTRUCTION: ENHANCING STUDENT MOTIVATION AND LEARNING OUTCOMES - Fitriani, Yara; Sofendi; Vianty, Machdalena (English Review: Journal of English Education, 2025)
Modern classrooms demand teaching approaches that address diverse learning needs. This study examines how transformative English teachers implement Differentiated Instruction (DI) to enhance student motivation and learning outcomes, combining adaptive pedagogy with equitable education practices. Using a qualitative case study design, the research focused on two experienced Indonesian English teachers trained in DI through the Guru Penggerak program. Semi-structured interviews explored their DI implementation strategies and impacts on learners. Results showed DI significantly boosts engagement when teachers tailor instruction to individual needs through flexible grouping, tiered assignments, and multimodal assessments. Students demonstrated greater motivation when expressing understanding through varied formats like videos, podcasts, or traditional essays. The approach also improved academic performance by aligning with different learning preferences and readiness levels. The study concludes DI creates inclusive classrooms that foster both academic growth and 21st-century skills when implemented effectively. Recommendations include investing in teacher training, providing DI resources, and incorporating flexible assessment policies. Future research should investigate DI's long-term effects across diverse educational contexts.